Skills or culture? An analysis of the decision to work by immigrant women in Italy - Antonio Accetturo; Luigi Infante (IZA Journal of Migration, 2013)
Activity and employment rates for immigrant women in many industrialised countries display a great variability across national groups. The aim of this paper is to assess whether this fact is due to a voluntary decision (i.e. large reservation wages by immigrants) or to an involuntary process (i.e. low labor market evaluation of their skills). This is done by estimating the reservation wage for each individual in a sample of immigrant women in Italy. Our results show that low activity and employment rates for certain national groups are not associated with high reservation wages. This implies that low participation should not be interpreted as a voluntary decision.
Keywords: J22; J61; J15; 330; reservation wages; female labor supply; cross-national differences